Perspektif Hak Asasi Manusia Dalam Konteks Negara Hukum - Cindy Salsabila Guritno; Emilia Susanti; Izzatul’Aisy; Mifta Yuljannah Pasaribu; Siti Nabila; Tiara Rahma Dani (Pusat Riset dan Inovasi Nasional, 2024)
This journal contains human rights perspectives in the context of the rule of law. This journal was created with the aim of (1) explaining the concept and characteristics of the rule of law, (2) explaining how the rule of law is in Indonesia, (3) explaining the nature of Human Rights (HAM), (4) explaining the history of the development of Human Rights (HAM). , (5) explains Human Rights (HAM) in Indonesia. This journal was created using the library research method, by collecting and analyzing material obtained from several books.